Local Migrant Integration Policies and Their Structural Mechanisms - Bargerová, Zuzana (Karolinum Press, 2023)
The publication explores migrant integration in the Czech Republic, Slovakia, Belgium (Flanders) and Germany (Bavaria) with the aim to understand the unique situational context of each country and to find opportunities for mutual learning and sharing of best practices. First, the realities in the four examined countries are introduced, focusing on strategic materials, key actors and mutual expectations from migrants and the receiving societies. The Czech Republic and Slovakia are inspected in greater detail as less information is generally available on the situation in the two countries. After exploring the countries' approaches to migrants (especially at the local level), the book presents unique inspirational practices that can be a source of inspiration to others. Finally, the publication examines the challenges faced by the four countries in terms of local integration of migrants, and gives a number of practical recommendations. The publication follows developments up to the end of 2021.